Distance covered and average speed of movement during the 2012 British Open under 21 real tennis final - Nic, J.; Racz, R.; Ronaldson, M.; Vuckovic, G. (World Congress of Performance Analysis of Sport IX, 2012)
Real tennis is the original racket sport from which lawn tennis descended. It is played indoors on a court which is not perfectly symetrical or standard in size (Figure 1). The scoring system (love, 15, 30 , 40, deuce) was copied by lawn tennis although sets are won in real tennis by sudden death to 6 games. Whilst the game`s origins are uncertain it is believed to have started in the 12th century and current rules maintain this heritige by regulating that the construction of the racket and balls remain unchanged. This often results in very fast shots being played, which do not bounce very high and are difficult to hit. Consequently it is expected that rallies will be shorter than other racket sports and there is no published data regarding distances and speeds. One match played at the Middlesex university court (96` long, 31'6" wide at the service end, 30' wide at the grille wall) was filmed using 7 HD cameras installed for analysis purposes. The images from the two overhead cameras (centred above each side of the court) were processed using SAGIT software (Perš et al., 2001) to automatically track the players` (both World ranked around no. 50) movements. Rally data tended to be positively skewed with outliers hence Wilcoxon Signed Ranks tests were used to determine differences. The match duration (75m 28s) consisted of 227 rallies (lasting an average of 8.49s (SD=6.75s) resulting in 42.55% ball in play time. The match winner covered a total of 2632m during rallies at an average of 11.59m per rally (SD=9.62m) which was significantly further (z=3.02, p<.01) than the loser (2481m during rallies at an average of 10.93m per rally (SD=10.08m)). This corresponded to a similar difference in velocity (z=3.82, p<.001) with the winner moving at an average velocity of 1.33m/s (SD=0.33m/s) in comparison to the loser (1.20m/s, SD=0.39m/s).